Carbon-enriched SiOC ceramics with hierarchical porous structure as anodes for lithium storage. (10th March 2021) - Xia, Kedong; Liu, Xiao; Liu, He; Lu, Yun; Liu, Zhenmin; Li, Yunling; Duan, Lingyao; Hou, Zhenyu; Li, Renlong; Wang, Deli
Abstract: Honeycomb-like carbon-enriched SiOC ceramics were prepared with tetraethoxysilane and phenyltriethoxysilane as sol–gel precursor, and followed by etching with NaOH. The microstructure evolution, chemical composition and lithium storage performance of SiOC ceramics were investigated. The phase separation of SiOC ceramics occurs as the elevation of pyrolysis temperature. The reaction of SiO4 units with NaOH not only generates hierarchical porous structure, but also increases the relative content of C and Si-O-C phase. The porous SiOC ceramic (H-SiOC-900) possesses a high specific surface area of 503.62 m 2 g −1 and pore volume of 0.41 cm 3 g −1, and delivers a high reversible capacity of 961 mAh g −1 and 480 mAh g −1 at the current density of 50 mA g −1 and 500 mA g −1, respectively. Although the reversible capacity of porous SiOC ceramics is improved as the increase of SiO3 C and SiO2 C2 microstructures, the C content determines the electrochemical performance of bulk and honeycomb-like SiOC ceramics.